Sticky problems in sugar processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Recent project reports indicate problems with the quality of cane sugar in Mauritius. The rising cost of labour has led to some manual operations such as the stripping of the cane to be dropped. Machines do little better, since they capture not just...